Lessons from CBD-COP16: NBSAP Accelerator and Agrobiodiversity Index to Achieve Conservation Goals - Masso, Cargele (CGIAR, 2024)
COP16 just finished, what’s at stake now for biodiversity? There are two key efforts used to move agendas forward and help with the implementation of the Kunming-Montreal Global Biodiversity Framework (KMGBF): the Agrobiodiversity Index and the NBSAP Accelerator.